Susceptibilities of Mycobacterium fortuitum biovariant fortuitum and the unnamed third biovariant complex to heavy-metal salts. - Wallace, R J (1984)
Fifty-three clinical isolates of Mycobacterium fortuitum were tested for susceptibility to heavy-metal salts and antimicrobial agents. The isolates exhibited a bimodal distribution for several heavy metals including mercury, whose resistance is often plasmid mediated. There was a biovariant difference in the incidence of resistance, and resistance to several metal ions was often observed together. There was no apparent relationship between resistance to heavy-metal salts and resistance to antimicrobial agents such as tetracycline.